Offshore Electric Ship Charging Station: a Techno-Economic Analysis - Cawas Phiroze Nazir (International Journal of Marine Engineering Innovation and Research, 2021)
Diesel emissions from ships are some of the largest contributors to greenhouse gas emissions (GHG).  This paper proposes the feasibility of implementing grid-like batteries- onboard ocean-going vessels along with an offshore electric charging station (OECS) to offer fully electric sailing across longer distances. The (OECS) is proposed to be built in deep waters along commercial shipping routes. Such an installation has a floating solar plant, in conjunction with a battery energy storage system to meet the charging demands of an all-electric ship (AES).   The technology was evaluated based on a case study of an AES cargo vessel traveling between Mumbai and Dubai with a one-stop midway (at an OECS) for recharging batteries. When compared to a diesel ship, the AES showed savings of  5,627,293liters of diesel/yr and a reduction of 19,823 tonnes of CO2. The study shows that the integration of an OECS along with the AES concept is feasible, and represents a major milestone in bringing emission-free technology to the marine sector.